Driving Non-Functional Requirements to Use Cases and Scenarios - Cysneiros, Luiz Marcio; Leite, Julio César Sampaio do Prado (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de Software, 2001)
Today, companies are continuously changing and improving their business strategies. As a consequence, stakeholders are demanding more flexible and complex software to be built. To handle this complexity, conceptual models have to describe aspects beyond entities and activities. Recent research has pointed out that dealing with goals in order to capture intentions associated with complex situations is a major aspect to handle this new reality [14]. Non-Functional Requirements are a particular class of these goals that has to be dealt with since the early stages of software development. Therefore, expressing these NFRs in use cases and scenarios models is a must. In this work we show a strategy to drive elicited NFR towards use cases and scenarios that reflect the functional requirements of the software. We tested our proposal through two case studies and the results suggest that our strategy can help developers to deal with complex conceptual models and might result in a more complete software specification and thus, to a shorter time-to-the-market.